A pure hedonic theory of utility and status: Unhappy but efficient invidious comparisons. (13th February 2019) - Courty, Pascal; Engineer, Merwan
Abstract: We examine status preferences where agents compare their own utility relative to the utilities of others. As long as status utility comparisons are not too intense, they do not affect either the competitive equilibrium or the set of efficient allocations. However, status utility comparison may substantially reduce average utility and dramatically increase utility inequality. Equating utility with happiness operationalizes the theory and provides an explanation of why invidious comparisons can generate so much unhappiness without much inefficiency. Our theory has very different welfare implications from other status theories, even when reduced form representations appear observationally equivalent.